Barriers to sustainable transport : institutions, regulation and sustainability - Rietveld, Piet; Stough, Roger (Transport, development and sustainability., 2005)
This book gives an international perspective on the role of institutions and regulations regarding national transport policy, local sustainable transport, international transport and freight transport.